2021
DOI: 10.1186/s13047-021-00481-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of cardiopulmonary resuscitation amongst New Zealand podiatrists: a web‐based survey

Abstract: Background Podiatrists in New Zealand have a duty of care to assist patients in an emergency, and current cardiopulmonary resuscitation (CPR) certification is a requirement for registration. However, it is unknown how competent and confident podiatrists are in administering CPR and how they would respond in an emergency. Having a health professional who has a competent knowledge of CPR and skills in basic life support, can improve survival rates from sudden cardiac arrest. Therefore, the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Doctors at an academic hospital in South Africa also exhibited inadequate CPR knowledge, primarily attributed to a lack of regular training opportunities [18]. In a study conducted among podiatrists in New Zealand, high levels of CPR confidence were reported, but gaps in CPR knowledge were identified despite having compulsory CPR certification [19]. Furthermore, a study conducted in Tanzania among healthcare providers from various departments highlighted poor CPR knowledge and skills, despite self-reported CPR experience [20].…”
Section: Discussionmentioning
confidence: 99%
“…Doctors at an academic hospital in South Africa also exhibited inadequate CPR knowledge, primarily attributed to a lack of regular training opportunities [18]. In a study conducted among podiatrists in New Zealand, high levels of CPR confidence were reported, but gaps in CPR knowledge were identified despite having compulsory CPR certification [19]. Furthermore, a study conducted in Tanzania among healthcare providers from various departments highlighted poor CPR knowledge and skills, despite self-reported CPR experience [20].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the availability of specialized technology, such as an Automated External Defibrillator (AED), CPR aims to sustain a circulation sufficient to protect brain function. Early, effective CPR has been demonstrated to save lives and enhance neurological outcomes for patients (Brenton-Rule et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The mean difference in the efficiency of the training program according to gender is revealed in Table4 4…”
mentioning
confidence: 99%